Introduction and Summary of the Two-Year and Five Year Plans Uttar Pradesh - Planning Commission (Planning Commission, 1951)
Until we regained our freedom ours was principally a Police State. It was perhaps natural for the foreigners to pursue a policy of exploitation in the interests of their own country. the effect of this policy, pursued over several generations, has been to leave the country economically, morally and socially backward. In this state of backwardness the scope for the development of various activities is almost unlimited.
Uttar Pradesh